Ion beam engineered hydrogen titanate nanotubes for superior energy storage application. (1st March 2021) - Das, Pritam; Das, Subhasish; Ratha, Satyajit; Chakraborty, Brahmananda; Chatterjee, Shyamal
Abstract: Nanotube or nanowire-based supercapacitors are having huge potentials as they offer large device-level energy density and they can withstand significant stress, which is important for building flexible and high-performance storage devices. The present work shows how we can exploit ion beam as a tool to create surface defects and porous structure besides enhancing charge-transfer property and surface area through large-scale joining among hydrogen titanate nanotubes and achieve enhancement of charge storage capacity and energy density. Self-assembled hydrogen titanate nanotubes have been hydrothermally synthesized on oxidized titanium foil and exposed to low energy (5 keV) Ar + ion-beam at different ion fluences, before detailed electrochemical analyses to validate their charge storage performance. Irradiated hydrogen titanate nanotubes showed exceptional charge storage performance in terms of specific capacitance, which is about 1572 F/g, at a very high mass-normalized-current of 10 A/g. The charge storage performance of irradiated hydrogen titanate nanotubes was found to be superior to the performance recorded for the pristine/unmodified nanotubes. The detailed experimental findings, further corroborated by first-principles calculations, provide clear insights regarding the enhanced charge storage performance in the case of irradiated nanotubes. We have also computed the work function of the material before and after O vacancy. Reduction in work function due to O vacancy supports improved charge storage performance due to irradiation. Factors like the induced oxygen vacancy, pore formation, improved surface area, and enhanced charge-transfer property play significant roles in the high charge storage performance of the irradiated samples. This study further demonstrates the potential of using the ion beam irradiation technique to tune the surface area, conductivity, and storage capacity of the supercapacitor electrode. Graphical abstract: Image, graphical abstract